2017
DOI: 10.18632/oncotarget.16382
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of iron overload-induced apoptosis and necrosis of bone marrow mesenchymal stem cells by melatonin

Abstract: Iron overload induces severe damage to several vital organs such as the liver, heart and bone, and thus contributes to the dysfunction of these organs. The aim of this study is to investigate whether iron overload causes the apoptosis and necrosis of bone marrow mesenchymal stem cells (BMSCs) and melatonin may prevent its toxicity. Perls’ Prussion blue staining showed that exposure to increased concentrations of ferric ammonium citrate (FAC) induced a gradual increase of intracellular iron level in BMSCs. Tryp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 44 publications
2
27
0
Order By: Relevance
“…Firstly, we found that iron exposure resulted in a reduction of cell viability, induction of ROS, and increasing of apoptosis in a dose-dependent manner in 1.1B4 cells that have been previously reported in other types of cell line such as HH4, human hematopoietic cells/mesenchymal cells, MC3T3-E1 cells, and MG-63 cells through different mechanisms (Li et al, 2016;Lu et al, 2013;Doyard et al, 2012;Yang et al, 2017;Ke et al, 2017). Many reports have been demonstrated that iron overload lead to increasing intracellular ROS and caused cell damage, which is concomitant with our results.…”
Section: Discussionsupporting
confidence: 66%
“…Firstly, we found that iron exposure resulted in a reduction of cell viability, induction of ROS, and increasing of apoptosis in a dose-dependent manner in 1.1B4 cells that have been previously reported in other types of cell line such as HH4, human hematopoietic cells/mesenchymal cells, MC3T3-E1 cells, and MG-63 cells through different mechanisms (Li et al, 2016;Lu et al, 2013;Doyard et al, 2012;Yang et al, 2017;Ke et al, 2017). Many reports have been demonstrated that iron overload lead to increasing intracellular ROS and caused cell damage, which is concomitant with our results.…”
Section: Discussionsupporting
confidence: 66%
“…4, 5). Because several studies have shown that iron overload induces apoptosis via activation of caspase3 46,47 , we studied the effect of Prx5 deficiency on iron overloadinduced neuronal cell death related to caspase3. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow mesenchymal stem cells (BMMSC), an important component of the bone marrow microenvironment and regulator of hematopoiesis, undergo programmed cell death and necrosis when exposed to excessive iron concentrations [53] and in mice exposed to high doses of iron dextran, impaired osteogenic differentiation of BMMSC along with reduced levels of VEGF and CXCL12 were observed [54]. On the other hand, osteoblasts, which play crucial roles in the maintenance of HSC pool, bone marrow microenvironment and ultimately regulate hematopoiesis [55], are also harmed by iron overload, as shown in a recent study reporting that iron overload impairs the growth and function of osteoblasts via inhibition of PI3K/AKT signal [39].…”
Section: Discussionmentioning
confidence: 99%